SAT0146 At diagnosis of rheumatoid arthritis, at-risk patients followed in ccp+ clinic showed milder disease activity than conventionally referred patients. (12th June 2018) - Duquenne, L.; Pentony, P.; Mankia, K.; Nam, J.; Hunt, L.; Tan, A. L.; Garcia-Montoya, L.; Emery, P.
Abstract : Background: Early treatment of rheumatoid arthritis (RA) improves clinical and radiological outcomes 1 . Risk stratification models can identify patients at high risk of developing RA, 2–5 which may lead to an extension of the window of opportunity. Whether identifying and following at-risk individuals improves outcomes after the development of RA however is yet to be determined. Objectives: The hypothesis is that patients followed in a specific at-risk clinic will have less severe disease at diagnosis than those referred via the conventional route if/when they develop RA. Methods: In two single-centre prospective observational cohorts, patients fulfilling the 2010 EULAR classification criteria for RA were compared on a demographic and clinical approach. The first group was composed of 59 patients positive for anti-cyclic citrullinated protein antibodies (CCP) with non-specific musculoskeletal symptoms, considered to be "at-risk of RA", who were followed until RA diagnosis. The second group was composed of 92 CCP positive RA patients referred to a standard 'Early Arthritis' rheumatology clinic. Results: Demographic data at RA development were consistent between both groups including smoking history and BMI. Immunological features were also similar. CCP titre: at risk median 193U/ml (IQR 41, 300), standard care 300U/ml (IQR 81, 300, p=0.176)). Rheumatoid factor (RF) titre: at risk median 84iU/mL (IQR 15, 223), standard care 87iU/mL (IQR18, 161, p=0.850). RF positivity: at risk 75%, standard care 70% (p=0.544). High-titre CCP blood levels: at risk 95%, standard care 97% (p=0.566). As shown in table 1, DAS28CRP score were significantly lower in the at risk group than in standard care, this was due to a difference in the general health Visual Analogue Scale score and the CRP levels. Patients in the at risk group also had fewer swollen large joints and reported significantly shorter time between onset of subjective joint swelling and diagnosis. There was no difference between the presence of erosions on ultrasound scans (at risk: 39%, standard care 38%, p=0.921). Conclusions: Patients who were diagnosed with RA while being followed in an at-risk cohort had milder disease activity and less pain than those diagnosed through standard referral despite equivalent demographics and serology. This reflects an earlier diagnosis and hence shorter exposure to inflammation. Follow-up will be required to see if these differences convert to long-term benefits. References: [1]van der Heide. Ann Intern Med1996;124(8). [2]Rakieh. Ann Rheum Dis2015;74(9). [3]Van de Stadt. Ann Rheum Dis2013;72(12). [4]Van Steenbergen. Ann Rheum Dis2016;75(10). [5]Nam JL. Ann Rheum Dis2016;75(12). Disclosure of Interest: None declared